“The Diseases of Astonishment”: Cotton Mather and Narrative Possession - Harshbarger, Scott (Narrative Works)

(untitled) (The University of New Brunswick, 2016)
It is generally accepted that Cotton Mather’s (1689/1914) account of the possession of the Goodwin children, published in Memorable Providences, helped to kindle the Salem witchcraft panic three years later (Hill, 2000; Reynolds, 2008). This article draws on historical scholarship, narrative theory, and cognitive science in order to throw light on the social conditions and cognitive processes whereby narrative content, genre, and practices can converge to destabilize identity, enabling in extreme cases a kind of narrative possession.